Fractional Wannier Orbitals and Tight-Binding Gauge Fields in Kitaev Honeycomb Superlattices with Flat Majorana Bands - K. B. Yogendra; G. Baskaran; Tanmoy Das (Physical Review X)
Fractional excitations hold immense promise for both fundamental physics and quantum technologies. However, constructing lattice models for their dynamics under gauge fields remains a formidable challenge due to inherent obstructions. Here, we introduce a novel and systematic framework for deriving low-energy lattice models of fractional orbitals coupled to tight-binding gauge fields. Departing from conventional geometric approaches, our method systematically eliminates the high-energy states via virtual hopping, thereby deriving the gauge potential and quantum metric through a superexchange mechanism. We demonstrate the framework by constructing Wannier orbitals for Majorana states and a tight-binding Z_{2} gauge field across various flux-crystalline phases in the Kitaev spin model on a honeycomb lattice. Our study reveals a striking phase transition between two nontrivial topological phases characterized by gapless flat band with extensive degeneracy. Furthermore, we develop a gauge-invariant mean-field theory for interacting Majorana orbitals, leading to a fractional Chern state. Our work establishes a general framework for gauge-mediated tight-binding models and a gauge-invariant mean-field theory for interacting fractional orbitals that can be readily extended to U(1), SU(N) lattice gauge theories.